The Effect of Drying and Storage on the Quality of Shallot (Allium cepa L. Aggregatum group) Bulbs - Rohimah Handayani Sri Lestari; Endang Sulistyaningsih; Aziz Purwantoro (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2018)
Post-harvest handling in shallot such as drying of bulbs can influence its quality during and after storage. The objective of this study was to determine the impact of drying and storage treatment on the quality of shallot bulbs during 12 weeks of storage . The study was carried out in Samiran hamlet, Parangtritis village, Bantul district, Special Region of Yogyakarta and Crop Science Laboratory of the Faculty of Agriculture, Universitas Gadjah Mada, from June until November 2016. It was arranged in factorial randomized complete block design (RCBD) and consisted of two factors. The first was the drying treatments: drying the bulbs on the field and on woven bamboo nets both plastic covered and uncovered. The second was the storage treatments: storing the bulbs in the farmer’s warehouse (31,030C±0,04 and RH of 60,50%±0,28), in air-conditioned room (22,40oC± 0,02 and RH of 61,60%±0,09), and at room temperature (30,47oC±0,03 and RH of 60,50%±0,12). Each treatment combination was replicated three times as blocks. The results showed that water content of all treatments were changing followed by fluctuating of the total soluble solid throughout the storage period while bulb firmness tended to decrease. Bulbs which were stored in air-conditioned rooms showed the highest percentage of sprouted bulbs, vigor index and germination rate than other treatments. Meanwhile, drying treatment did not give significant influence.